The Consumer price index in the Philippines, 1994-. (Manila National Statistics Office, 1994)
It provides factual Consumer Price Index (CPI) figures from 1957 to 1994 (with 1988 as base year) on the national and regional scale and by the major commodity group.
This publication is the maiden issue of the Annual Report on the Consumer Price Index in the Philippines. It represents CPI figures from 1957 to 1994 (with 1988 as base year) on the national and regional levels and by major commodity group. Inflation rates and purchasing power of the peso are likewise presented. A textual analysis with graphical presentation is provided to have a clear picture of movement over time. Technical notes are included in the Appendix for a better understanding of how the CPI is generated. Planners, businessmen, researchers and others will find much use for the time series data presented in this volume. (Foreword)
Keywords: Consumer price indexes -- Philippines